In silico Exploration of Bioactive Compounds from Withania somnifera as Inhibitor for Alpha Delta Bungarotoxin of Bungarus candidus Venom - Prabasari, Kartika; Kurnianingsih, Nia; Kurniawan, Nia (Universitas Brawijaya, 2023)
The antivenom for Malayan krait (Bungarus candidus) venom has not yet been available in Indonesia, leading to many fatal snakebite cases. Alternative treatment approaches using medicinal plants are needed to be explored. This study investigated the potential of medicinal plants’ natural bioactive compounds as toxic alpha-delta bungarotoxin protein inhibitors in B. candidus venom. The approach taken is using the 3D structure of the alpha-delta protein of bungarotoxin B. candidus predicted by SWISS-MODEL. Knapsack Family Database and PubChem were used for bioactive compounds datamining. ADME analysis and drug-likeness of the compounds were carried out with SWISS-ADME. Docking between alpha-delta-Bungarotoxin protein and bioactive compounds was carried out with Pyrx 0.9.5. Visualization of docking results was performed with PyMOL and Discovery Studio 2016 was used to evaluate docking interactions. The docking results showed that a compound with the potential inhibitor of alpha-delta bungarotoxin came from Ashwagandha (Withania somnifera) with a binding energy ranging from -6.6 to -6.9. The compound with the best inhibitor potential, namely withanolide D, was seen from the stability of the interaction based on hydrogen bonding at three amino acid residues: THR59, SER62, and THR63. The evaluation is supported by the results of molecular dynamics simulations which show stability in almost all aspects. Our results suggest the potential for exploratory research in the field of bioinformatics related to bioactive compounds from herbal plants as an alternative to antivenom.